2017
DOI: 10.1111/disa.12256
|View full text |Cite
|
Sign up to set email alerts
|

Flooding: what is the impact on pregnancy and child health?

Abstract: Floods are the most common type of natural disaster in both developed and developing countries and have led to extensive morbidity and mortality throughout the world. Worldwide, over the past 30 years, flooding has claimed the lives of more than 200,000 people and affected more than 2.8 billion others. The impact of flooding on health varies among populations and depends primarily on vulnerability and the kind of event experienced. It severely disrupts livelihoods and has a significant impact on the health of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(33 citation statements)
references
References 115 publications
(189 reference statements)
0
33
0
Order By: Relevance
“…31 A review of the literature on floods as a major natural disaster reveals negative maternal/child health sequelae such as low birth weight, mental health disorders, PTSD, and stillbirth. 32 Qualitative studies regarding natural disasters or health crises also corroborate these findings: pregnant women have expressed distress about body image, family planning, and prevention concerns, particularly regarding risks for birth defects regarding the Zika outbreak; 33 and concerns across a variety of domains in the aftermath of Hurricane Katrina, such as the health of the child and family, housing and finances, breastfeeding, mental health, and loss. 34 In the qualitative findings in our study, many women commented about the need to remain calm and engage in self-care, not only for their own wellness but also for the wellness of their child and family.…”
Section: Discussionmentioning
confidence: 88%
“…31 A review of the literature on floods as a major natural disaster reveals negative maternal/child health sequelae such as low birth weight, mental health disorders, PTSD, and stillbirth. 32 Qualitative studies regarding natural disasters or health crises also corroborate these findings: pregnant women have expressed distress about body image, family planning, and prevention concerns, particularly regarding risks for birth defects regarding the Zika outbreak; 33 and concerns across a variety of domains in the aftermath of Hurricane Katrina, such as the health of the child and family, housing and finances, breastfeeding, mental health, and loss. 34 In the qualitative findings in our study, many women commented about the need to remain calm and engage in self-care, not only for their own wellness but also for the wellness of their child and family.…”
Section: Discussionmentioning
confidence: 88%
“…Fewer studies have examined the impact of natural disasters on pregnancy related health conditions such as gestational hypertension and preeclampsia, which may also be impacted by stress [31,32]. Research from both the United States and Japan have found elevated preeclampsia or gestational hypertension, following natural disasters (hurricanes, floods, earthquakes), but these analyses could be sensitive to regional differences or time trends [27,[33][34][35].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, personality factors, as long-standing traits existing before and after, could predict an individual’s vulnerability to develop PTSD and we suggested it to be a potential vulnerability factor for developing long-term PTSD after the Wenchuan earthquake. In addition, trauma factors of an earthquake associated with the trauma severity should also be taken into account as the rate of PTSD can vary with severity of the event and the duration of trauma exposure, which was one of the most important post-disaster stressors for PTSD (26, 27). For instance, Chen and Xu et al (28) investigated the role of personality traits and subjective exposure experiences in PTSD among 20,749 children who experienced the Wenchuan earthquake and found that, besides neuroticism, subjective exposure experiences are also risk factors for PTSD.…”
Section: Introductionmentioning
confidence: 99%